2010
DOI: 10.3945/jn.109.118075
|View full text |Cite
|
Sign up to set email alerts
|

Higher Maternal Plasma Folate but Not Vitamin B-12 Concentrations during Pregnancy Are Associated with Better Cognitive Function Scores in 9- to 10- Year-Old Children in South India

Abstract: Folate and vitamin B-12 are essential for normal brain development. Few studies have examined the relationship of maternal folate and vitamin B-12 status during pregnancy and offspring cognitive function. To test the hypothesis that lower maternal plasma folate and vitamin B-12 concentrations and higher plasma homocysteine concentrations during pregnancy are associated with poorer neurodevelopment, 536 children (aged 9-10 y) from the Mysore Parthenon birth cohort underwent cognitive function assessment during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
155
5
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(170 citation statements)
references
References 46 publications
8
155
5
2
Order By: Relevance
“…Our findings that moderate folate levels in early pregnancy are associated with higher birth weight regardless of race/ethnicity are consistent with previous studies, [14][15][16][17][18][19][20][21][22][23][24]50 although an equally large number of studies from Europe, Asia and the US [25][26][27][28][29][30][31] have not confirmed these associations. Reasons for discordant findings are unclear.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings that moderate folate levels in early pregnancy are associated with higher birth weight regardless of race/ethnicity are consistent with previous studies, [14][15][16][17][18][19][20][21][22][23][24]50 although an equally large number of studies from Europe, Asia and the US [25][26][27][28][29][30][31] have not confirmed these associations. Reasons for discordant findings are unclear.…”
Section: Discussionsupporting
confidence: 88%
“…13 In humans, evidence of associations between maternal folate concentrations and fetal growth is conflicting, as high levels have been linked to both low and high birth weight, [14][15][16][17][18][19][20][21][22][23][24] while other studies found no associations. [25][26][27][28][29][30][31] Extremes of the birth weight distribution have been associated with a wide range of childhood and adultonset chronic diseases and conditions including obesity, impaired glucose tolerance, type 2 diabetes, coronary artery disease, congestive heart failure and some cancers.…”
Section: Introductionmentioning
confidence: 99%
“…What has been comparatively ignored is the contribution of adverse conditions during pregnancy, such as moderate maternal undernutrition during early pregnancy, on the developmental programming of neurodegenerative diseases. Of related interest is a study that has linked inappropriate maternal nutrition with cognitive impairment in children (20) and preliminary reports associating adverse pregnancy with an increased prevalence of depression and schizophrenia in later life (21).…”
Section: Long-term Consequencesmentioning
confidence: 99%
“…This suggests a need for balanced nutrition. These two vitamins also influence the offspring neurodevelopment (Veena et al, 2010;Godbole et al, 2009;Bhate et al, 2008). Higher maternal homocysteine concentration (caused by vitamin B 12 and folate deficiency) is associated with foetal growth restriction.…”
Section: Nutrition and Foetal Programmingmentioning
confidence: 99%
“…However, if they face overnutrition in postnatal life (urban migration), they are likely to develop obesity and hyperglycaemia at a young age, and gestational diabetes in girls that propagates the obesity and diabetes phenotype ("fuel-mediated teratogenesis") (Freinkel, 1980). Rapidly transitioning countries like India seem to have both cycles running simultaneously, feeding into an explosive epidemic of NCDs (Silverman et al, 1995;Yajnik, 2009;Krishnaveni et al, 2010).…”
Section: Nutrition and Foetal Programmingmentioning
confidence: 99%